Mussel Shutdown: Does the Fear of Trematodes Regulate the Functioning of Filter Feeders in Coastal Ecosystems? - Selbach, Christian; Mouritsen, Kim N. (Frontiers in Ecology and Evolution, 2020)
Parasite infections have negative impacts on their hosts. Accordingly, many organisms try to detect and avoid infective parasite stages, leading to changes in host behaviour or physiology. Such non-consumptive effects on host traits can have cascading impacts on whole ecosystems but remain largely overlooked. Here, we discuss the potential impacts of the presence of free-living trematode stages on blue mussels Mytilus edulis, an important ecosystem engineer in coastal habitats, and highlight the ecological implications of these interactions. Specifically, we discuss how parasite avoidance behaviour can regulate the filtration activity of these bivalves in coastal ecosystems and show how even moderate changes in mussel behaviour can lead to far-reaching shifts in energy flow. Such processes might be further amplified under future climate change developments, since both parasite abundance and biotic productivity are highly temperature dependent. Overall, we hypothesize that, in addition to their more evident consumptive impacts, trematodes act as cryptic ecosystem engineers by shaping bivalve filtration processes via non-consumptive effects. Due to our still very limited understanding of these parasite-mediated processes, we outline key questions for future research directions. We hope this perspective will help encourage new efforts to empirically investigate these fascinating processes that can be crucial regulatory forces in complex ecological systems.